Folding of Hitchin Systems and Crepant Resolutions. (19th January 2021) - Beck, Florian; Donagi, Ron; Wendland, Katrin
Abstract: Folding of ADE-Dynkin diagrams according to graph automorphisms yields irreducible Dynkin diagrams of $ABCDEFG$ -types. This folding procedure allows to trace back the properties of the corresponding simple Lie algebras or groups to those of $ADE$ -type. In this article, we implement the techniques of folding by graph automorphisms for Hitchin integrable systems. We show that the fixed point loci of these automorphisms are isomorphic as algebraic integrable systems to the Hitchin systems of the folded groups away from singular fibers. The latter Hitchin systems are isomorphic to the intermediate Jacobian fibrations of Calabi–Yau orbifold stacks constructed by the 1st author. We construct simultaneous crepant resolutions of the associated singular quasi-projective Calabi–Yau three-folds and compare the resulting intermediate Jacobian fibrations to the corresponding Hitchin systems.